Homicídio de crianças e adolescentes cometidos por cuidadores - Nunes, Leticia Felipe (2014)
This research intended to extend the subject of domestic violence, highlighting a little-studied nationally topic: the murder of children and adolescents by their biological or non- biological parents or their caregivers. The main research goal was characterize a sample of biological or non- biological parents or caregivers who committed children and adolescents murder – their biological or non-biological children. Besides the basic identification data it was sought to describe the modus operandi and the murder motive. It was also aimed to examine murderers parenting practices due to the victims, as well as to their own parents submitted them back in their childhood. To do so, two steps were perfomed: 1) Documentary Research of 600 record of proceedings of the 2nd Jury Court of Curitiba; that leads to 11 selected records judged (1,83%) by Art.121 or 123 of the Brazilian Penal Code, in the State of Paraná, and 2) The application of Parenting Styles Inventory – IEP (Gomide, 2011) with 4 prisoners in Penitentiary Units. Taking into account the characteristics of the group of 11 murderersof the study 1, they are men mostly aged between 20 and 25 years, with incomplete primary education, and their victims are children under 12 years old. victims. The motives can be grouped into: 1) disorders and syndromes; 2) maltreatment; 3) behavioral changes associated with revenge, jealousy and compassion for the child and adolescent and 4) family history of violence. The modus operandi with use of sharp objects, manual choking and gun. The four participants in Study 2 were answered the IEP, they were aged from 35 to 47 years, completed elementary school and their victims were under 12 years; they committed the homicide with the use of sharp instruments, firearms and hands. IEP showed maternal risk practices, indicating that they underwent to negative parenting practices by their mothers including extreme physical abuse. These results show that it is necessary a careful look when faced with children who suffer from abuse and violence, and parents / caregivers who have a history of domestic violence or psychiatric problems, and therefore work on the prevention baseline, such as training in parenting practices to prevent future crimes of this nature.